SARS-CoV-2 vaccination, ABO blood group and risk of COVID-19: population-based cohort study - Joel G Ray; Alison L Park (BMJ Open, 2022)
Objective To compare outcomes between O and non-O blood groups, and by modified RNA (mRNA) and adenovirus-vectored (Ad-V) vaccines.Design Population-based cohort study.Setting All of Ontario, Canada. Linked data sets captured clinical encounters, vaccinations and laboratory testing for SARS-CoV-2.Participants Individuals aged 12+ years with known ABO blood group and free of SARS-CoV-2 before 15 January 2021.Main outcomes measures The main exposure, first SARS-CoV-2 vaccination, was modelled in a time-varying manner. O and non-O blood group was known prior to vaccination. SARS-CoV-2 infection, and severe COVID-19 (hospitalisation or death), were assessed starting 14 days after vaccination, up to 27 June 2021.Results 2 472 261 individuals were included. 1 743 916 (70.5%) had at least one vaccination, of which 24.6% were fully vaccinated. Those vaccinated were more likely to be women, older in age, residing in a higher-income area and have higher rates of certain comorbid conditions, like cancer, diabetes and hypertension. Relative to unvaccinated, after receiving their first mRNA (adjusted HR (aHR) 0.46, 95% CI 0.44 to 0.47) or Ad-V (aHR 0.49, 95% CI 0.44 to 0.54) vaccine, the risk of SARS-CoV-2 infection was lower, as was severe COVID-19 (aHR 0.29, 95% CI 0.20 to 0.43 (mRNA); aHR 0.29, 95% CI 0.26 to 0.33 (Ad-V)). Stratifying by blood group produced similar results. For example, after first mRNA vaccination, the aHR of severe COVID-19 was 0.31 (95% CI 0.27 to 0.36) among non-O blood groups, and 0.27 (95% CI 0.22 to 0.32) among O blood groups, relative to unvaccinated. Fully vaccinated individuals had the lowest risk of SARS-CoV-2 and severe COVID-19.Conclusions SARS-CoV-2 infection and severe COVID-19 are reduced by vaccination. This effect does not vary by vaccine type or blood group, but is more pronounced among fully, than partially, vaccinated individuals.